THE IMPACT OF MATERIAL DESCRIPTION GIVEN BY TEACHER WITH LKS MATERIAL ON CIVICS LEARNING ACHIEVEMENT IN FIRST GRADE OF MTS AL-MUHAJIRIN, SOUTH LAMPUNG - ni'ma lida; Adelina Hasyim; yunisca nurmalisa (Jurnal Kultur Demokrasi, 2012)
The purpose of the research is to reveal the breakdown of the valgus material presented with material in question teachers LKS and reveals the impact of the alignment of bio-material presented with material about the teacher in the learning achievements against LKS In Grade VII in the MTs Al-Muhajirun, Ketapang, Lampung Regency South in the lessons of 2012/2013. The methods used in this study is the method descriptions, with data sources 6 people including 5 pupils and one teacher and 30 students for achievement test. Engineering data collection using subject interview, documentation and tests. Data analysis using qualitative analysis Based on the study results were obtained: 1. most discrepancies description material presented with material in question teachers LKS, because there is a problem in this matter is not described LKS guru, and there is also a description of the material that described the teacher is not in the matter of LKS. 2. There are differences impact description material presented with material about the teacher in the learning achievements against LKS PKn. This means getting lazy students seek additional material from other sources then his achievements are getting lower. And the more diligent students find the material from a source other then the higher achievements.Keywords: Teacher Description Material, LKS Problem Material, and Civics Learning Achievement